Remember the teeth! Cutaneous manifestation of odontogenic sepsis: A case study - Lilli Ladurner; Maather Al Zadjali; Manjit Dhillon (JPRAS Open)
We present the case of a 21-year-old male with a 3-year history of an isolated 1 × 1 cm purulent lesion on the left cheek, on a background of mild acne. Despite topical treatments, the lump persisted, discharging frank pus regularly. Microbiology swabs and an incisional biopsy were unremarkable. A further two excisions were performed but wound healing was poor, and the lesion returned.Upon referral to Oral and Maxillofacial Surgery, examination of the oral cavity suggested a dental abscess from the maxillary molar tooth. This was confirmed radiographically on an orthopantomogram and cone beam CT. He had been asymptomatic from his heavily filled teeth which may have silently lost vitality. The dental abscess tracked towards the cheek forming a discharging fistula. The offending teeth were extracted, and the cutaneous lesion healed spontaneously, leaving a 2 × 1.8 cm disfiguring, indented scar.This case highlights that dental abscesses can fistulate cutaneously and that an odontogenic cause for cutaneous lesions around the mouth should be considered in the differentials.